2010
DOI: 10.1016/j.cell.2010.09.013
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β and Insulin Signaling Regulate Reproductive Aging via Oocyte and Germline Quality Maintenance

Abstract: SUMMARY Reproductive cessation is perhaps the earliest aging phenotypes humans experience. Similarly, C. elegans’ reproduction ceases in mid-adulthood. Although somatic aging has been studied in both worms and humans, mechanisms regulating reproductive aging are not yet understood. Here we show that TGF-β Sma/Mab and Insulin/IGF-1 signaling regulate C. elegans reproductive aging by modulating multiple aspects of the reproductive process, including embryo integrity, oocyte fertilizability, chromosome segregatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
487
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(519 citation statements)
references
References 66 publications
23
487
1
Order By: Relevance
“…By day 8, some hermaphrodites began displaying detectable and even extreme degenerative changes in the gonad, as noted in previous studies (Garigan et al 2002;Herndon et al 2002;Luo et al 2010). The distal gonad displayed a decreased diameter and contained fewer germ cell nuclei ( Figure 5D).…”
Section: Phenotypic Analysis Of Mutations That Delay Reproductive Agisupporting
confidence: 55%
See 2 more Smart Citations
“…By day 8, some hermaphrodites began displaying detectable and even extreme degenerative changes in the gonad, as noted in previous studies (Garigan et al 2002;Herndon et al 2002;Luo et al 2010). The distal gonad displayed a decreased diameter and contained fewer germ cell nuclei ( Figure 5D).…”
Section: Phenotypic Analysis Of Mutations That Delay Reproductive Agisupporting
confidence: 55%
“…Garigan et al (2002) showed that the distal gonad displays age-related increases in cavities and grainy material and decreases in the number of nuclei, and these changes were analyzed by assigning scores from 1 to 5 on the basis of the degree of deterioration. Luo et al (2010) reported a similar analysis of the distal gonad and an analysis of the proximal gonad that showed age-related decreases in oocyte size and increases in cavities and cluster formation. These changes were analyzed by assigning scores of normal, mild, or severe.…”
Section: Phenotypic Analysis Of Mutations That Delay Reproductive Agimentioning
confidence: 84%
See 1 more Smart Citation
“…Two C. elegans TGF-β ligands have been well characterized: DAF-7 and DBL-1. Whereas DAF-7 regulates multiple physiological traits, including diapause stage (dauer) entry, metabolism (8)(9)(10)(11), DBL-1 controls body morphology, innate immunity, and reproductive aging (9,12,13). Here we report that the activity of DBL-1 is critical for adult animals to learn to avoid the smell of pathogenic bacteria.…”
mentioning
confidence: 86%
“…Continued identification of new oocyte-specific genes and their functional annotation is providing additional insight into the molecular mechanism involved in folliculogenesis, oogenesis, fertilization and early embryogenesis (Bettegowda et al, 2007;Wells et al, 2008;Luo et al, 2010). Several techniques such as differentialdisplay reverse transcription-PCR, microarray hybridization, serial analysis of gene expression and cDNA library construction have been used to reinforce the inventory of oocyte-expressed genes.…”
Section: Introductionmentioning
confidence: 99%